2018
DOI: 10.1073/pnas.1801213115
|View full text |Cite
|
Sign up to set email alerts
|

SAMHD1 suppresses innate immune responses to viral infections and inflammatory stimuli by inhibiting the NF-κB and interferon pathways

Abstract: Sterile alpha motif and HD-domain-containing protein 1 (SAMHD1) blocks replication of retroviruses and certain DNA viruses by reducing the intracellular dNTP pool. SAMHD1 has been suggested to down-regulate IFN and inflammatory responses to viral infections, although the functions and mechanisms of SAMHD1 in modulating innate immunity remain unclear. Here, we show that SAMHD1 suppresses the innate immune responses to viral infections and inflammatory stimuli by inhibiting nuclear factor-κB (NF-κB) activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
201
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(214 citation statements)
references
References 50 publications
6
201
1
Order By: Relevance
“…4666) or heatinactivated HIV-1 was used as controls. Heat-inactivated HIV-1 was generated by incubating the virus at 65°C for 1 h as described (45). Activated primary CD4 ϩ T-cells were infected with HIV-1 NL4 -3 (MOI of 1), and cells were harvested at 96 hpi for total RNA extraction using RNAeasy kit (Qiagen).…”
Section: Hiv-1 Infection Assays and Treatment With Heat-inactivated Hmentioning
confidence: 99%
“…4666) or heatinactivated HIV-1 was used as controls. Heat-inactivated HIV-1 was generated by incubating the virus at 65°C for 1 h as described (45). Activated primary CD4 ϩ T-cells were infected with HIV-1 NL4 -3 (MOI of 1), and cells were harvested at 96 hpi for total RNA extraction using RNAeasy kit (Qiagen).…”
Section: Hiv-1 Infection Assays and Treatment With Heat-inactivated Hmentioning
confidence: 99%
“…The transcription factor NF‐κB plays an important role in regulating the inflammatory response . NF‐κB consists of five proteins, including p65, p50, p52, c‐Rel, and RelB.…”
Section: Introductionmentioning
confidence: 99%
“…By decreasing the pool of available dNTPs to a level insufficient to support reverse transcription, SAMHD1 was able to restrict a broad range of retroviruses, including HIV-1, during the early reverse transcription step [30,31]. In addition, SAMHD1 might have the ability to modulate antiviral activity by inhibiting the NF-B and interferon pathways [32]. Regarding HTLV-1, Gramberg et al [33] demonstrated that, in macrophages and cycling CD4+ T cells, the virus was not blocked by SAMHD1 and that Tax was produced.…”
Section: Samhd1mentioning
confidence: 99%